2015
DOI: 10.1007/s11999-014-4062-3
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Vancomycin to Cefazolin Prophylaxis Is Associated With Acute Kidney Injury After Primary Joint Arthroplasty

Abstract: Background With increasing prevalence of methicillinresistant Staphylococcus aureus (MRSA) in patients undergoing hip and knee arthroplasty, some have advocated a dual-antibiotic regimen including vancomycin as prophylaxis against surgical site infections. However, routine administration of vancomycin may result in impaired renal functions in susceptible patients. Questions/purposes The purpose of this study was to determine whether patients receiving antibiotic prophylaxis with cefazolin and vancomycin have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 43 publications
4
59
0
7
Order By: Relevance
“…In a study of 1828 hip and knee arthroplasty patients, Courtney et al . reported a higher rate of acute kidney injury in patients receiving dual prophylaxis than those given cefazolin alone (13% versus 8%, P = 0.002) . Additionally, in the same cohort of patients, Sewick et al .…”
Section: Discussionmentioning
confidence: 80%
“…In a study of 1828 hip and knee arthroplasty patients, Courtney et al . reported a higher rate of acute kidney injury in patients receiving dual prophylaxis than those given cefazolin alone (13% versus 8%, P = 0.002) . Additionally, in the same cohort of patients, Sewick et al .…”
Section: Discussionmentioning
confidence: 80%
“…Courtney et al. also showed that patients who received combined vancomycin and cefazolin as prophylaxis for primary joint arthroplasty had a significantly higher risk of acute kidney injury as compared to patients who received cefazolin alone …”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of vancomycin versus cefazolin or other antistaphylococcal antibiotics as surgical site prophylaxis has not been studied in prospective clinical trials in patients who undergo CIED placement or revision. Ascompared to cefazolin, vancomycin is less effective in vitro and in vivo against methicillin‐susceptible Staphylococcus aureus (MSSA), has no Gram‐negative coverage, and has nephrotoxicity risk (which can occur even with one dose) . Therefore, vancomycin is not used as routine surgical site prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to assess the efficacy, safety, and cost of these interventions in order to implement prevention protocols that will reduce infection rates in a safe and cost-effective way. More is not necessarily better, as was shown with the addition of vancomycin to cephazolin prophylaxis in primary joint arthroplasty [1]. We should also be aware that a patient with a history of a PJI has increased risk of subsequent PJI at a different site.…”
mentioning
confidence: 97%